Special Group Discussion: The impact of nutritional status in the new era of COVID-19: patients, nutrients and lifestyle - Dian Novita Chandra; bernie medise; Listya Tresnanti Mirtha; Juwalita Surapsari (Indonesian Nutrition Association, 2022)
The COVID-19 pandemic has created a new era, it altered many aspects of lives all over the world. Many studies found the changes in nutrient and dietary intake, habits and patterns, also food and nutrition supplement consumption in many countries. Changes in lifestyle, physical activity and excercise patterns were observed in many studies around the world as outcome of lockdown, isolation, or community movement restriction regulations imposed by governments during the COVID-19 pandemic .